2017
DOI: 10.1186/s12891-017-1633-y
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of tranexamic acid in revision total knee arthroplasty: a meta-analysis

Abstract: BackgroundThere is no consistent conclusion regarding the efficacy and safety of the intravenous administration of tranexamic acid (TXA) for reducing blood loss in revision total knee arthroplasty (TKA). We performed a meta-analysis of comparative trials to evaluate the efficacy and safety of TXA in revision TKA.MethodsWe conducted a search of PubMed, EMBASE, The Cochrane Library and Web of Science for randomized controlled trials (RCTs) and non-RCTs. Two authors selected the studies, extracted the data, and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 16 publications
0
8
0
1
Order By: Relevance
“…Es fand sich ein reduzierter perioperativer Blutverlust (gewichtete mittlere Differenz [MD] -504,90 ml, 95 %-CI -620,89 bis -388,92 ml; p < 0,0001) sowie eine geringere Rate allogener Bluttransfusionen (MD -1,43; 95 %-CI -1,69 bis -1,17; p < 0,0001). Zwei aktuelle Metaanalysen bestätigen diesen Effekt für den simultanen bilateralen Kniegelenksersatz sowie bei Revisionsoperationen [72,82]. Anzumerken ist, dass in den meisten Studien TXA nicht zu Beginn der Operation, sondern erst kurz vor Öffnen der "Blutsperre" verabreicht wurde, um einer allfällig prothrombogenen Wirkung vorzubeugen.…”
Section: Txa In Der Orthopädieunclassified
“…Es fand sich ein reduzierter perioperativer Blutverlust (gewichtete mittlere Differenz [MD] -504,90 ml, 95 %-CI -620,89 bis -388,92 ml; p < 0,0001) sowie eine geringere Rate allogener Bluttransfusionen (MD -1,43; 95 %-CI -1,69 bis -1,17; p < 0,0001). Zwei aktuelle Metaanalysen bestätigen diesen Effekt für den simultanen bilateralen Kniegelenksersatz sowie bei Revisionsoperationen [72,82]. Anzumerken ist, dass in den meisten Studien TXA nicht zu Beginn der Operation, sondern erst kurz vor Öffnen der "Blutsperre" verabreicht wurde, um einer allfällig prothrombogenen Wirkung vorzubeugen.…”
Section: Txa In Der Orthopädieunclassified
“…The use of tranexamic acid decreases hematoma formation and blood loss. A recent meta-analysis reported that the use of tranexamic acid was related to a shorter length of hospital stay 9) . The use of a multimodal analgesic cocktail gives effective pain relief and functional recovery, which may also shorten the hospital stay 10) .…”
Section: Introductionmentioning
confidence: 99%
“…To reduce bleeding, techniques, such as skin heating, gentle soft tissue dissection during surgery, use of a new bipolar electrocautery device, use of cardiac stent, and if not contraindicated, discontinuation of anticoagulant drugs, and use of preoperative intra-and postoperative tranexamic acid drugs, can be applied (18,19).…”
Section: Discussionmentioning
confidence: 99%